Relationship of the AKR1B1 rs759853 and rs9640883 with the development of diabetic retinopathy (Ukrainian Journal of Ophthalmology, 2026)
Background: In type 2 diabetes mellitus (DM2), hyperglycemia activates the polyol pathway of glucose metabolism, resulting in accumulation of sorbitol and fructose. Polymorphism of aldose reductase (a key enzyme of the poliol pathway) gene (AKR1B1) influences the activity of the polyol pathway and might be associated with the development of diabetic retinopathy (DR).Purpose: To identify any association of the polymorphisms influencing the activity of aldose reductase gene (rs759853 and rs9640883 of AKR1B1) with DR in the Ukrainian population.Materials and Methods: In total, 311 individuals were involved in the study. Group 1 (control group) was composed of 107 ophthalmologically normal subjects. Group 2 contained 76 patients with stage 1 DR (i.e., showing no fundus changes). Group 3 consisted of 64 patients diagnosed with non-proliferative DR (NPDR), and Group 4 was composed of 64 patients diagnosed with proliferative DR (PDR). The TaqMan Mutation Detection Assays were used to analyze polymorphic DNA loci in a Real-Time PCR System 7500.Results and Discussion: In Ukrainian population, rs759853 and rs9640883 of AKR1B1 were associated with the development of DR. The mutant A allele and AA genotype at the rs759853 increased the odds (OR=2.8 and OR=5.2, respectively; р
Keywords: diabetic retinopathy; AKR1B1; rs759853; rs9640883